ADAPTATION AND PSYCHOMETRICS OF POSITIVE AND NEGATIVE SUICIDE IDEATION INVENTORY - Saba Yasien, Zaeema Riaz Ahmad (Pakistan Journal of Clinical Psychology, 2015)
Objective: Positive and negative suicide ideation inventory (PANSI) assess both protective and risk factors of suicidal ideation simultaneously. The current study aimed to translate/ adapt, and establish the psychometric properties of PANSI comprised of two subscales named as positive ideation (PI) and negative suicide ideation (NSI). Place of study: Institute of Clinical Psychology, University of Karachi Sample and Method: For the translation / adaptation of PANSI into Urdu, methods of forward and back-translation were followed. Psychometric properties were assessed by administering Urdu version of PANSI on adolescents aged 16 to 19 years old. To estimate reliability, Cronbach’s alpha was applied and Convergent validity was assessed through the correlation with Aga Khan Anxiety-Depression scale (Ali, Jehan, Reza & Khan, 1998) and Beck Hopelessness scale (Ayub, 2009). Results: Cronbach’s alpha for PANSI-PI (.73) and PANSI-NSI (.89) found adequate. Significant association of PANSI-NSI was found with Aga Khan Anxiety Depression scale (.44) and Beck Hopelessness scale (.25). PANSI-PI was found to be negatively correlated with Aga Khan Anxiety Depression scale (-.15) and Beck Hopelessness scale (-.28). In addition, construct validity was supported by principal component analysis. Conclusion: The Urdu version of PANSI is found to be reliable, valid, equivalently useful for measuring suicidal ideation and protective factors compared to the original inventory among Pakistani population.